Efektivitas Aktivitas Permainan Tradisional dalam Mengembangkan Kecakapan Hidup Sosial Siswa - Gunawan, Sani; Subarjah, Herman; Berliana, Berliana; Ma’mun, Amung (Jurnal Porkes, 2025)
The increasing use of gadgets and the decline in direct social interaction have led to a decrease in cooperation, communication, and social-emotional skills among adolescents, which has become a critical issue in character education. This study aims to test the effectiveness of a structured traditional game intervention program in developing the social life skills of high school students. The method used is a quasi-experiment with a one-group pretest-posttest design. A total of 30 students participated in the intervention for 16 sessions involving traditional Indonesian games (gobak sodor, bentengan, engklek, galasin) combined with guided reflection to facilitate skill transfer. Measurements were taken using the Life Skills Scale for Sport, which covers eight dimensions of life skills. Data analysis was performed using a paired sample t-test and effect size calculation (Cohen's d). The results showed a significant increase in the total social life skills score (p < 0.001) with a very large effect size (d = 1.51). The highest increase occurred in the dimensions of teamwork (+2.7 points) and leadership (+1.5 points). The conclusion of this study proves that pedagogically designed traditional games not only function as recreational activities but are also effective, contextual, and culture-based learning media for strengthening the social-emotional competencies of adolescents.